1995
DOI: 10.1002/jlb.57.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 and human monocyte activation

Abstract: The recognition of the monocyte/macrophage-activating properties of IL-2 has broadened our image of the biological effects of this lymphokine from those of a T cell growth factor to those of a molecule with pleiotropic effects. The detailed analysis of the mechanisms of action of IL-2 including its biological effects on different cell types and the regulation of its receptors has increased dramatically the spectrum of the biological responses that can be modified by IL-2. The regulation of the expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 104 publications
0
41
0
2
Order By: Relevance
“…The activity of these cytokines on monocytes is not mitogenic, but instead modulates cellular function (53). For example, treatment of monocytes with IL-2 will activate tumor cytocidal programs (54).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of these cytokines on monocytes is not mitogenic, but instead modulates cellular function (53). For example, treatment of monocytes with IL-2 will activate tumor cytocidal programs (54).…”
Section: Discussionmentioning
confidence: 99%
“…The IL-2␤ chain is critical for IL-2 activation of monocytes and is expressed in more than 90% of these cells. It has been suggested that IL-2R␣ is important for the formation of high-affinity binding sites responding to IL-2 [41][42][43]. Although the IL-2R␤ chain is shared with IL-15 receptor, and IL-2R␥ chain is also common to IL-4, IL-7, IL-9, and IL-15 [23], we studied the expression of all three IL-2R subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine has diverse stimulatory effects on a variety of immune cells including the activation of natural killer (NK) cells, induction of the lymphokine-activated killer (LAK) cells [43], activation of monocytes [44] and macrophages [42], and the activation of CD8 + cytotoxic T lymphocytes (CTLs) [45]. Previous studies have shown that IL-2 can induce T-cell production of IFN-γ [46], a very potent immunomodulator that can inhibit tumor growth by direct induction of apoptosis [47], and through its ability to stimulate CTLs [48], macrophages [49], NK cells [50] and to increase the expression of the major histocompatibility complex class II molecules (MHC class II) [51].…”
Section: Antibody-(il-2) Fusion Proteinsmentioning
confidence: 99%